2007
DOI: 10.1016/j.sysarc.2006.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of caching in a distributed digital library system

Abstract: Today independent publishers are offering digital libraries with fulltext archives. In an attempt to provide a single user-interface to a large set of archives, the studied Article-Database-Service offers a consolidated interface to a geographically distributed set of archives. While this approach offers a tremendous functional advantage to a user, the fulltext download delays caused by the network and queuing in servers make the user-perceived interactive performance poor. This paper studies how effective cac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…richness and variety of resources available; and . ease of search through various search engines (Appleton, 2006;Hollmann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…richness and variety of resources available; and . ease of search through various search engines (Appleton, 2006;Hollmann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cooper also designed a model, for user's time and the process, it adopted cluster analysis and time series analysis, and found that the query number, time, results number, result number of different users had different characteristics (Hollmann, Ardö & Stenström, 2007). Through data analysis, it understood and mastered the characteristics of digital library users, predicted the future trend to study the behavior law of digital library users.…”
Section:  Tracking Records Of Individual Usementioning
confidence: 99%
“…One of the authentication mechanisms is client authentication. Client authentication means making users prove that they are who they say they are before allowing them access to a particular area (Guenther, 2001). It is the second step from two steps.…”
Section: Use Of Data Mining and Data Protection Technology In The 21 ...mentioning
confidence: 99%
“…Professor Michael Cooper, had mined and analyzed record data of catalog use of the digital library in California University, and found several types of users, users of real use the directory, the network robbert only collect data for retrieval services, general visitors just visit the website but not find the directory, their duration of stay is different. Cooper also designed a model, for user's time and the process, it adopted cluster analysis and time series analysis, and found that the query number, time, results number, result number of different users had different characteristics [14]. Through data analysis, it understood and mastered the characteristics of digital library users, predicted the future trend to study the behavior law of digital library users.…”
Section: Construction Of Classification Commonly Uses Machine Learninmentioning
confidence: 99%